KELINCAHAN ORGANISASI : PERAN KETERAMPILAN DIGITAL DAN KEPEMIMPINAN AGILE PADA UMKM - Diah Ayu Kusumawati; Sri Anik (Master of Management, Mataram University, 2023)
This study discusses the role of digital skills and agile leadership that can affect organizational agility. Companies that have digital skills will influence organizational agility and are supported by agile leadership as a moderation, so they will be better prepared in facing the era of digitalization. This research was conducted by testing SEM (Structural Equation Modeling) using the help of SmartPLS statistical software. This research was conducted by survey method by distributing questionnaires to 250 MSMEs in Central Java, Indonesia. The results of this study have a positive and significant relationship between workforce transformation and e-readiness in digital skills. Agile leadership can moderate the relationship between digital skills and organizational agility of MSME in Central Java. The conclusion is that digital skills and agile leadership have a role in increasing organizational agility of MSMEs in Central Java. Keywords: Workforce Transformation, E-readiness, Digital Skill, Agile Leadership, Organizational Agility, MSMEs Penelitian ini membahas peran digital skill dan agile leadership yang dapat mempengaruhi organizational agility. Perusahaan yang memiliki digital skill akan mempengaruhi organizational agility dan didukung oleh agile leadership sebagai moderasi, sehingga lebih siap dalam menghadapi era digitalisasi. Penelitian ini dilakukan dengan pengujian SEM (Structural Equation Modeling) menggunakan bantuan software statistik SmartPLS. Penelitian ini dilakukan dengan metode survei dengan menyebarkan kuesioner kepada 250 UMKM di Jawa Tengah, Indonesia. Hasil penelitian ini memiliki hubungan yang positif dan signifikan antara workforce transformation dan e-readiness dalam digital skill. Agile leadership dapat memoderasi hubungan antara digital skill dengan organizational agility UMKM di Jawa Tengah. Kesimpulannya bahwa digital skill dan agile leadership berperan dalam meningkatkan organizational agility UMKM di Jawa Tengah.